1, 2‐Boryl Migration Enables Efficient Access to Versatile Functionalized Boronates. Issue 9 (3rd March 2022) - Jiang, Xia‐Min; Liu, Xin‐Ru; Chen, Ang; Zou, Xi‐Zhang; Ge, Jian‐Fei; Gao, De‐Wei
Abstract: Organoboronates are synthetically useful and highly valuable building blocks in synthetic and medicinal chemistry. Two‐electron reactions allow for the rapid construction of organoboronates via nucleophilic 1, 2‐boron shift of boron ate complexes or MIDA‐mediated 1, 2‐boryl migration. Radical approaches through 1, 2‐boron shift of neutral boronic esters or boron ate complexes have been demonstrated to be feasible, providing complementary methods to access these privileged scaffolds. In this Review, recent achievements are highlighted and future opportunities are discussed, with an emphasis on different operative modes of catalysis and reaction pathways. Abstract : Preparation of organoboronates is highly valuable in synthetic chemistry, material science and medicinal chemistry. In this Review, recent advances to access this privileged scaffold via 1, 2‐boryl migration are discussed. Two complementary methods by ionic or radical mechanism have been systematically introduced.